The Clinical Outcomes of Arthroscopic Tenotomy versus Tenodesis with Medium-to-Massive Rotator Cuff Tear in the Elderly: A Retrospective Study - Song K; Lu G; Cai M; Sun Q (Clinical Interventions in Aging)
Kaihang Song,* Guanghua Lu,* Ming Cai, Qi Sun Department of Orthopedics, Shanghai Tenth People’s Hospital, School of Medicine, Tongji University, Shanghai, 200072, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ming Cai; Qi Sun, Email cmdoctor@163.com; tjdxsq@163.comPurpose: Shoulder arthroscopic repair of rotator cuff tears with simultaneous treatment of lesions of the long head of the biceps tendon has become increasingly accepted. However, the clinical outcomes between tenotomy and tenodesis remain unclear. This study aimed to compare the efficacy of tenotomy and tenodesis combined with rotator cuff repair in elderly patients with medium-to-massive rotator cuff tears.Patients and Methods: We conducted a retrospective trial of patients aged > 60 years with medium-to-massive rotator cuff tears who underwent arthroscopic rotator cuff repair with tenotomy or tenodesis. This study included 96 patients: 47 in the tenotomy group and 49 in the tenodesis group. At 3 and 6 months after surgery and at the last follow-up, the American Shoulder and Elbow Surgeons (ASES) score, Constant-Murley score (CS score), anterior shoulder pain (VAS score), elbow flexion strength and supination strength, and complications were recorded.Results: At 3 months postoperatively, ASES score, CS score and strength of elbow flexion of the tenodesis group were significantly better than those of the tenotomy group. In addition, the VAS score is 4.4 ± 1.4 and 3.3 ± 1.3 in the tenodesis and tenotomy respectively (p = 0.039). At the final follow-up, despite no significant statistical differences in ASES scores, CS scores, VAS scores, and flexion strength between the two groups, the variation in the above items in the tenodesis group was statistically lower than that in the tenotomy group. No difference was observed in the rates of complications and revision between the groups.Conclusion: For people over 60 years of age with medium to massive rotator cuff tears, postoperative shoulder function of tenodesis is superior to tenotomy, and functional recovery is relatively more stable after tenodesis than after tenotomy.Keywords: tenodesis, tenotomy, aged population, arthroscopy, rotator cuff tear